Patterns of health services utilization in the last two weeks of life among cancer patients: Experience in an Australian academic cancer center. Issue 6 (11th July 2017) - Ong, Wee Loon; Khor, Richard; Bressel, Mathias; Tran, Phillip; Tedesco, Jo; Tai, Keen Hun; Ball, David; Duchesne, Gillian; Foroudi, Farshad
Abstract: Aim: To report the trend in end‐of‐life health services (HS) utilization among cancer patients treated in a large Australian academic cancer center over a 12‐year period. Methods: This is a retrospective study of cancer patients treated at the Peter MacCallum Cancer Centre (PMCC), who had documented death between January 2002 and December 2013. Using administrative and billing database, we report on the utilization of different categories of HS within two weeks of death: diagnostic investigations (pathology and radiology), inpatient and outpatient services, and potentially futile interventions (PFI, which include radiotherapy, chemotherapy and surgery). Results: Of the 27 926 "active" cancer patients in the study (i.e. those with medical contact at PMCC in the last year of life), 6368 (23%) had documented HS utilization within two weeks of death. 11% and 9% had pathology and radiology investigations respectively, 14% had outpatient clinic appointments, and 7% had hospital admissions. There were 2654 patients (10%) who had PFI within two weeks of death – 2198 (8%) had radiotherapy, 287 (1%) chemotherapy and 267 (1%) surgery. We observed peak HS and PFI utilization in 2004, which then dropped to its lowest in 2009/2010. Conclusion: Experience in an Australian cancer center suggests approximately one in four "active" cancer patients had HS utilization, and one in ten had PFI, within two weeks of death. The implementation of palliative care guidelines may reduce some of these potentially wasteful and futile interventions.